Effect of Temperature, Velocity Gradient and I.V. Heparin on in Vitro Blood Coagulation and Platelet Aggregation - Dintenfass, L; Rozenberg, M. C (Thrombosis and Haemostasis, 1967)
A study of blood coagulation was carried out by observing changes in the blood viscosity of blood coagulating in the cone-in-cone viscometer. The clots were investigated by microscopic techniques.Immediately after blood is obtained by venepuncture, viscosity of blood remains constant for a certain “latent” period. The duration of this period depends not only on the intrinsic properties of the blood sample, but also on temperature and rate of shear used during blood storage. An increase of temperature decreases the clotting time ; also, an increase in the rate of shear decreases the clotting time.It is confirmed that morphological changes take place in blood coagula as a function of the velocity gradient at which such coagulation takes place. There is a progressive change from the red clot to white thrombus as the rates of shear increase. Aggregation of platelets increases as the rate of shear increases.This pattern is maintained with changes of temperature, although aggregation of platelets appears to be increased at elevated temperatures.Intravenously added heparin affects the clotting time and the aggregation of platelets in in vitro coagulation.